Motivational factors influencing the use of massive open online courses (MOOCS) for continuing professional development: a systematic literature review - Clement Buyut, Veronica; Abdullah, Salfarina; Abdullah, Rusli; Atan, Rodziah (Science and Engineering Research Support Society, 2019)
Since the term Massive Open Online Courses (MOOCs) was first coined in 2008, it has been dubbed as the disruptive technology in higher education. MOOCs have attracted massive number of users as the provider of open education to unlimited number of participants. As we embrace the impacts from the rapid transformations in the fourth industrial revolution, there has been a greater need to prepare the workforce to face the challenges that come with the change and one way is to see education as a development tool. While online learning is not new, MOOCs are undeniably making quality education accessible even to working adult learners who are looking for the opportunities of upskilling and reskilling their work talent. There is little research on MOOCs as supporting tools for Continuing Professional Development (CPD)in corporate settings, with researches mainly focusing on the learners from higher learning institutions. Therefore, this paper aims to analyze the literature on the motivational factors that influence the use of MOOCs for CPD. Findings show that the relevant literature is limited. The papers included in the review were classified into motivational factors from employers and employees’ perspectives. Both categories identified professional development as one of the key factors influencing the use of MOOCs within the organizations.